Hubungan Tingkat Pengetahuan Dengan Sikap Pencegahan Peningkatan Kadar Kolesterol Pada Lansia di Wilayah Kerja Puskesmas Kartasura - Viona Putri Giwani; Kartinah Kartinah (Politeknik Kementerian Kesehatan Banjarmasin, 2026)
Abstrak Cholesterol represents a significant contributing factor to the development of ischemic heart disease and ischemic stroke. It is divided into two categories: high-density lipoprotein (HDL), commonly referred to as good cholesterol, and low-density lipoprotein (LDL), known as bad cholesterol. This research aims to examine the correlation between the level of knowledge and attitudes toward preventing increased cholesterol levels among elderly individuals. The study applied a quantitative approach using a cross-sectional design. The target population included older adults residing in the Kartasura Public Health Center area, encompassing those with both normal and high cholesterol levels, during the period from July to September 2025. Fifty participants were recruited through purposive sampling, with eligibility criteria including being 60 years of age or older and willing to complete the questionnaire. The study utilized validated and reliable instruments to assess knowledge and attitudes. The results are expected to enhance understanding of how knowledge and attitudes relate to efforts in preventing elevated cholesterol levels among the elderly.